2015
DOI: 10.1186/s40200-014-0127-9
|View full text |Cite
|
Sign up to set email alerts
|

Phylloquinone supplementation improves glycemic status independent of the effects of adiponectin levels in premonopause women with prediabetes: a double-blind randomized controlled clinical trial

Abstract: BackgroundVitamin K, as a cofactor in the gamma carboxylation of certain glutamic acid (Gla) residues, has been related to glucose metabolism and insulin sensitivity. Osteocalcin, also known as bone γ-carboxyglutamic acid, increases β-cell proliferation as well as insulin and adiponectin secretion, which improve glucose tolerance and insulin sensitivity. Thus, the purpose of the present study was to examine the possible role of adiponectin as a mediator of glucose homeostasis following phylloquinone supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 24 publications
(21 reference statements)
4
80
0
Order By: Relevance
“…Although the reasons for this finding are not entirely clear we hypothesize that the convenience associated with sensor glucose readings, compared with blood glucose testing, prompted more frequent testing. This supports a recent study reporting younger participants as being “too busy” for finger-stick testing [32]. HbA1c level was unchanged for intervention participants ≥65 years.…”
Section: Discussionsupporting
confidence: 87%
“…Although the reasons for this finding are not entirely clear we hypothesize that the convenience associated with sensor glucose readings, compared with blood glucose testing, prompted more frequent testing. This supports a recent study reporting younger participants as being “too busy” for finger-stick testing [32]. HbA1c level was unchanged for intervention participants ≥65 years.…”
Section: Discussionsupporting
confidence: 87%
“…Recent clinical studies have shown that vitamin K1 improves glycemic status in premonopausal women with prediabetes [14]. Studies have also shown that vitamin K1 reduces coronary artery calcification in type 2 diabetic patients [15] and in another study vitamin K1 (phylloquinone) was able to reduce the risk of type 2 diabetes [16].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to differences in the characteristics of participants and in the forms and dosages of vitamin K used. Heterogeneity became nonsignificant when the study by Rasekhi et al32 was excluded ( I 2 =0%, P =0.89). In this study, adiponectin level was significantly increased with vitamin K supplementation 32.…”
Section: Discussionmentioning
confidence: 98%
“…Heterogeneity became nonsignificant when the study by Rasekhi et al32 was excluded ( I 2 =0%, P =0.89). In this study, adiponectin level was significantly increased with vitamin K supplementation 32. The observed effect may be attributable to osteocalcin, which acts directly on adipocytes, resulting in adiponectin secretion 2528.…”
Section: Discussionmentioning
confidence: 98%